Online Probelm-Based Learning to Enhace Student Creativity in Physics Learning - Azyyati Azyyati; Dwi Sulisworo (Jurnal Ilmiah Pendidikan Fisika, 2022)
This study aims to determine the increase in students' mastery of concepts and creative thinking skills after implementing the problem-based learning model. The sample in this study were students of class VIII MTs Ad-Diinul Qayyim West Lombok using a qualitative approach and the type of classroom action research. The material used in this research is Substance Pressure. This research was conducted in the second (even) semester of the 2018/2019 academic year. The instruments used in this study include 1) observation sheets on the implementation of learning by the teacher; 2) student activity observation sheets; 3) the concept mastery test instrument, and the creative thinking skill test instrument in the form of essay questions. The results showed that using a problem-based learning model could improve conceptual mastery and creative thinking skills, with the following scores: For knowledge of concepts in the first cycle, a score of 65.52% was obtained, and the second cycle was 89.65%. Meanwhile, for creative thinking skills using a test in the form of an essay, 37.93% was obtained, and the second cycle was 93%.